2008
DOI: 10.5194/bg-5-1641-2008
|View full text |Cite
|
Sign up to set email alerts
|

North Pacific-wide spreading of isotopically heavy nitrogen during the last deglaciation: Evidence from the western Pacific

Abstract: Abstract. Sedimentary δ 15 N records in two IMAGES cores (MD012404 and MD012403) retrieved from the Okinawa Trough (OT) in the western North Pacific reveal deglacial increases with two peaks occurring during the Bølling/Allerød and the Preboreal/early Holocene periods. These peaks are synchronous with previously reported δ 15 N peaks in the Eastern Tropical North Pacific, although the amplitudes (from 3.8 to 5.8‰) are much smaller in the OT. Similar δ 15 N values for the last glacial maximum and the late-Holoc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 66 publications
1
25
0
Order By: Relevance
“…The deglacial δ 15 N maximum in the SCS record, that is about 0.5‰ higher than the average glacial value, is most likely to derive from changes in mean ocean nitrate δ 15 N. Many of the eastern Pacific records in the water column denitrification regions show δ 15 N declines subsequent to the early deglacial rise associated with increase in the regional denitrification rate (Figure 4a) [ Altabet et al , 1995, 1999, 2002; Ganeshram et al , 1995, 2000; Robinson et al , 2007]. In the Caribbean Sea FB‐ δ 15 N record as well as in a number of bulk sedimentary δ 15 N records at regions away from the denitrification zones [e.g., Kao et al , 2008] (black curve in Figure 4b), such a deglacial maximum is observed, in apparent synchrony with the deglacial increase in water column denitrification in the eastern Pacific [ Brunelle et al , 2007; Galbraith et al , 2008], suggesting a global nitrate δ 15 N maximum linked to deglacial changes in denitrification. Modeling results indicates that the early deglacial maximum in mean ocean nitrate δ 15 N is likely to be driven mostly by a delay between increased water column denitrification and increased sedimentary denitrification, which produces a maximum in the water column to sedimentary denitrification ratio [ Deutsch et al , 2004].…”
Section: Interpretation and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The deglacial δ 15 N maximum in the SCS record, that is about 0.5‰ higher than the average glacial value, is most likely to derive from changes in mean ocean nitrate δ 15 N. Many of the eastern Pacific records in the water column denitrification regions show δ 15 N declines subsequent to the early deglacial rise associated with increase in the regional denitrification rate (Figure 4a) [ Altabet et al , 1995, 1999, 2002; Ganeshram et al , 1995, 2000; Robinson et al , 2007]. In the Caribbean Sea FB‐ δ 15 N record as well as in a number of bulk sedimentary δ 15 N records at regions away from the denitrification zones [e.g., Kao et al , 2008] (black curve in Figure 4b), such a deglacial maximum is observed, in apparent synchrony with the deglacial increase in water column denitrification in the eastern Pacific [ Brunelle et al , 2007; Galbraith et al , 2008], suggesting a global nitrate δ 15 N maximum linked to deglacial changes in denitrification. Modeling results indicates that the early deglacial maximum in mean ocean nitrate δ 15 N is likely to be driven mostly by a delay between increased water column denitrification and increased sedimentary denitrification, which produces a maximum in the water column to sedimentary denitrification ratio [ Deutsch et al , 2004].…”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…(a) Bulk sedimentary δ 15 N records from each of the major water column denitrification zones: the eastern Pacific off Chile [ De Pol‐Holz et al , 2006], the eastern tropical North Pacific (Santa Barbara Basin [ Emmer and Thunell , 2000] and Mexican Margin [ Ganeshram et al , 1995]), and the Arabian Sea off Oman [ Altabet et al , 2002]. (b) δ 15 N records from the western Pacific: MD97–2142 foraminifera‐bound δ 15 N record from the South China Sea (this study) and two bulk sedimentary δ 15 N records, MD98–2181 from the western equatorial Pacific off Mindanao [ Kienast et al , 2008] and MD012404 from the Okinawa Trough [ Kao et al , 2008]. (c) Foraminifera‐bound δ 15 N records from ODP Site 999 in the Caribbean Sea, as well as from surface sediments at three other tropical N. Atlantic sites, near Barbuda Antiqua, Great Bahama Banks, and Little Bahama Banks (error bars indicate variations in FB‐ δ 15 N among these three sites) [ Ren et al , 2009].…”
Section: Interpretation and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is still a lack of firm sedimentary record in WP showing signals from the WCD zones. For example, most δ 15 N records in the WP, e.g., the South China Sea (SCS), the Sulu Sea (SS), and the Okinawa Trough (OT), exhibit much less or even unchanged temporal variability (<2‰) [ Kienast , 2000; Horikawa et al , 2006; Kao et al , 2008]. The invariant δ 15 N records (∼5‰) in the SCS have been even interpreted as representing a constant mean oceanic δ 15 N during the late Quaternary [ Kienast , 2000], and hence a minor impact of WCD zones.…”
Section: Introductionmentioning
confidence: 99%
“…Longer timescale records of δ 15 N along the NE Pacific margin indicate that glacial-interglacial variations in the extent of denitrification have persisted for the last several million years, where cooler climate periods are associated with weak or negligible denitrification (Liu et al, 2008;Altabet et al, 1999). In the Equatorial Pacific, Pena et al's 500 ka B.P.…”
Section: Enhanced Nutrient Supply During the Deglaciationmentioning
confidence: 99%